Strategi Memikat Hati Publik; Membentuk Citra dan Opini Publik di Lembaga Pendidikan Islam - Anwar, Ach. Syafiul; M. Irsyad Maulana; Imam Muslimin (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In an increasingly complex digital era, Islamic educational institutions face the challenge of building a positive image and favorable public opinion. This study aims to analyze effective strategies for shaping the image and public opinion of Islamic educational institutions, with the research questions: what is meant by building image and public opinion in the context of Islamic educational institutions, and what strategies can be implemented to foster public trust? The methodology employed is a literature review, including tool preparation and critical analysis of relevant literature. The findings indicate that building a positive image requires high integrity, quality service, trusted leadership, and the application of educational exhibitions as an effective communication medium. Six main strategies that can be implemented include honesty in communication, provision of quality services, strengthening leadership, developing human resources, applying competitive strategies, and utilizing educational exhibitions. Success in building a positive image not only enhances the institution's reputation but also contributes to increased attractiveness and public trust, enabling Islamic educational institutions to establish harmonious relationships with the community and support sustainable institutional growth. This research is expected to provide insights for the managers of Islamic educational institutions in implementing appropriate strategies.